A TAXONOMIC REVISION OF THE AFROTROPICAL SPECIES OF THE WEEVIL GENUS CIONUS (COLEOPTERA: CURCULIONIDAE) - Caldara, Roberto; Košťál, Michael (Zootaxa, 2023)
The Afrotropical species of the genus Cionus Clairville, 1798 are revised and 52 species are recognized as valid. Thirty-one species are described as new to the science: twenty-five from the continental subregions (C. concavifrons sp. n., C. coniungens sp. n., C. cretaceus sp. n., C. diaboli sp. n., C. fimbriatus sp. n., C. frater sp. n., C. friedmani sp. n., C. geometricus sp. n., C. hirtellus sp. n., C. intermedius sp. n., C. latruncularius sp. n., C. limosus sp. n., C. longinasus sp. n., C. mimeticus sp. n., C. natalensis sp. n., C. nhlosanicus sp. n., C. oberprieleri sp. n., C. oculatus sp. n., C. schuelei sp. n., C. stalsi sp. n., C. tanzanicus sp. n., C. tenuepilosus sp. n., C. terrosus sp. n., C. transvaalicus sp. n., C. zimbabwicus sp. n.) and six from Madagascar (C. callosus sp. n., C. convexiusculus sp. n., C. guttula sp. n., C. planus sp. n., C. variolosus sp. n., C. verrucosus sp. n.). The following new synonymies are proposed: Cionus chilianthi Marshall, 1941 syn. n. of C. angulicollis Rosenschoeld, 1838, C. virgatus Rosenschoeld, 1838 syn. n. and C. decorus Boheman, 1845 syn. n. of C. nubilosus Rosenschoeld, 1838, C. leucostictus griseus Fairmaire 1903 syn. n. of C. leucostictus Fairmaire, 1897. Lectotypes of Cionus albidus Rosenschoeld, 1838, C. alluaudi Hustache, 1920, C. angulicollis Rosenschoeld, 1838, C. catenatus Fairmaire, 1897, C. compactus Fairmaire, 1903, C. coriaceus Fairmaire, 1903, C. decorus Boheman, 1845, C. ebeninus Hustache, 1956, C. histrio Rosenschoeld, 1838, C. ingratus Fåhraeus, 1871, C. leucostictus Fairmaire, 1897, C. leucostictus griseus Fairmaire, 1903, C. notatus Rosenschoeld, 1838, C. nubilosus Rosenschoeld, 1838, C. perlatus Faust, 1885, C. pustulatus Fåhraeus, 1871, C. tristis Boheman, 1838, C. usambicus Faust, 1889, C. vicarius Hustache, 1939 and C. virgatus Rosenschoeld, 1838 are designated. The “variety” maculithorax Voss, 1960 of Cionus pardus Marshall, 1941 is considered an unavailable name. Description or redescription, comparative morphology, distribution, biological notes and key to all Afrotropical species are given. Photos of habitus in dorsal, of aedeagus in ventral and lateral, and of the apex of penis in dorsal view are reported for each species.